Porfiry Afanasyevich Dibrova: at the origins of scientific pomiculture in the Urals - T. N. Slepneva; A. V. Shlyavas (Труды по прикладной ботанике, генетике и селекции, 2021)
Porfiry Afanasyevich Dibrova was one of the first scientists and breeders standing at the origins of scientific pomiculture in the Urals. He was the author of 23 cultivars of apple, six of pear, one of sour cherry, and one of black currant. In the 1940s, he was the leader of collecting missions exploring the local assortment of fruit and berry crops in 50 districts of Sverdlovsk and Molotov (Perm) Provinces, and the Udmurt Republic. P.A. Dibrova was one of the authors of the first standard set of fruit and berry cultivars for the abovementioned areas. He studied regularities in the inheritance of valuable agronomic and biological traits of fruit crops and identified promising sources for apple and pear breeding. He launched the main plant breeding trends in the Middle Urals, now followed by contemporary breeders: the development of highly winter-hardy cultivars of apple and pear with fruiting precocity, stable yields, excellent fruit quality, and improved biochemical composition in fruits.